Utility of urine as a clinical specimen for the diagnosis of pulmonary tuberculosis in people living with HIV in Addis Ababa, Ethiopia - Alemu Chemeda (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2019)
Background: Tuberculosis is a common cause of mortality and morbidity among people living with HIV/AIDS. Despite the increased prognosis of tuberculosis among HIV infected patients, diagnosis of pulmonary tuberculosis (PTB) smear microscopy has a low sensitivity due to low bacterial load in a sputum specimen of HIV patients. Having alternative specimens for increasing detection of Mycobacterium tuberculosis (Mtb) is very important. Objective: The aim of this study was to evaluate the efficacy of urine as clinical specimen for the diagnosis of pulmonary tuberculosis in people living with HIV. Method: A total of 117 HIV-seropositive individuals from three public health facilities in Addis Ababa, Ethiopia were enrolled consecutively from December 2013 to July 2014. A total of 117 paired morning sputum and urine samples were simultaneously collected from anti-retroviral therapy (ART) naïve PTB suspected individuals living with HIV. Both sputum and urine samples were processed for culture using Lowenstein-Jensen medium, and the left was subjected to PCR using RD9 primers. Chi-square test and kappa value were used to compare different methods used. Result: Out of 117 suspected PTB HIV-infected people, sputum culture alone detected more mycobacterial isolates 33 (28.2%) than the urine specimen alone 17 (14.5%). Of the 33 patients positive for sputum culture, 13 patients were observed as a urine culture positive. Of the 84 individuals negative for mycobacterial by sputum culture, four (4.8%) were urine culture positive and thus, the sensitivity, and the agreement between urine culture as compare to sputum culture were 39.4% and 0.49, respectively. On the other hand, the sensitivity of RD9-based PCR directly on urine was 72.7% by considering sputum culture as a reference standard. Moreover, RD9-based PCR directly on sputum detected 9 (7.7%) individuals who were sputum culture negative for M. Tuberculosis. The detection rate of M. tuberculosis from urine in patients those who couldn't produce sputum were 9(34.6%). Conclusion: PCR and culture examination of urine samples also can improve the detection rate of M. tuberculosis in PTB suspected HIV positive individuals. Keywords: Diagnosis, PCR, Pulmonary tuberculosis, TB-HIV infected, Tuberculosis